2018
DOI: 10.3102/0002831218803872
|View full text |Cite
|
Sign up to set email alerts
|

Building Linguistically Integrated Classroom Communities: The Role of Teacher Practices

Abstract: Adolescents’ peer networks tend to segregate by relative language proficiency, but students from all linguistic backgrounds benefit academically from classroom peer relationships both within and across English learner (EL) and non-EL classified groups. We drew upon social network analysis of student survey data in 46 English and math middle school classrooms and qualitative analysis of a subset of these classrooms (N = 10) to address the following: (a) How do demographics differ in classrooms with more or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…Taking this a step further, the lack of effects of emotional support and the weak and inconsistent effects of classroom organization on the peer network outcomes in the present study may indicate that more explicit practices are needed to promote bridging across language status groups within the classroom, beyond CLASS-S’s general domains of good teacher-student interaction quality. For instance, in a mixed methods analysis, Authors (2019) compared qualitative observations of teachers’ practices across the school year in classrooms with low/decreasing integration across language status groups to classrooms with high/increasing integration. They found that teachers with high/increasing language integration in their classroom peer network were more likely to assign more complex collaborative tasks, support students in learning to work together, and show curiosity about other languages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking this a step further, the lack of effects of emotional support and the weak and inconsistent effects of classroom organization on the peer network outcomes in the present study may indicate that more explicit practices are needed to promote bridging across language status groups within the classroom, beyond CLASS-S’s general domains of good teacher-student interaction quality. For instance, in a mixed methods analysis, Authors (2019) compared qualitative observations of teachers’ practices across the school year in classrooms with low/decreasing integration across language status groups to classrooms with high/increasing integration. They found that teachers with high/increasing language integration in their classroom peer network were more likely to assign more complex collaborative tasks, support students in learning to work together, and show curiosity about other languages.…”
Section: Discussionmentioning
confidence: 99%
“…Classrooms are an important space in which students have the potential to make same- and cross-language-status connections (Kibler et al, 2019; Williams, 2001). It has long been theorized that teachers play a role in how their classroom peer network develops, such as what relationships form, how many relationships form, and the climate of peer relationships—for example, positive and supportive, or negative and aggressive (see Audley-Piotrowski et al, 2015; Farmer et al, 2016; Farmer, McAuliffe Lines, & Hamm, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the points where student goals and curricularized goals meet at the bottom and top of our figure are important but relatively underemphasized areas in language teaching research. These practices—which aim to foster engagement through meeting students’ needs or desires for playfulness, community, and pride—are factors that have been theorized as supporting multilingual students’ sense of classroom community and individual belonging (Kibler et al., 2019). These are important drivers in the process of language development because they focus on not just what students can do with language, but also how they establish who they are and how they relate to others.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous research has demonstrated that teachers have the power to influence classroom network characteristics through instructional and classroom management decisions (Gest & Rodkin, 2011), and that interventions aimed at improving teachers’ peer network management can effectively foster more productive and cooperative network characteristics (Hamm et al., 2011). Future research can identify circumstances and specific teacher practices that best foster SNE and linguistic integration within linguistically diverse classrooms (see Kibler et al., 2019 for one such effort), and develop interventions to effectively facilitate these processes.…”
Section: Discussionmentioning
confidence: 99%
“…We examined data from a study of sixth, seventh, and eighth grade math and English language arts (ELA) classrooms from two linguistically diverse middle schools in the South-Atlantic region of the United States (Kibler et al, 2019).…”
Section: Participantsmentioning
confidence: 99%